2021
DOI: 10.1038/s41598-021-96576-1
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the genetic basis of genotype-by-environment interactions for grain yield and main agronomic traits in Iranian bread wheat landraces and cultivars

Abstract: Understanding the genetic basis of performance stability is essential to maintain productivity, especially under severe conditions. In the present study, 268 Iranian bread wheat landraces and cultivars were evaluated in four well-watered and two rain-fed conditions for different traits. According to breeding programs, cultivars were in a group with a high mean and stability in terms of GY, GN, and SW traits, while in terms of PH, they had a low mean and high stability. The stability of cultivars and landraces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 82 publications
3
11
0
Order By: Relevance
“…The present study clealy demonstrated that GEI significant contribution to the phenotypic variance, which suggests that genotypes performed differently in each environment and that their performance rank differ across test sites. The significant effect of GEI have been noted in several research reports on differents traits, including grain yield, in durum wheat landraces and cultivars [29,80], in line with the resuls of the present study.…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…The present study clealy demonstrated that GEI significant contribution to the phenotypic variance, which suggests that genotypes performed differently in each environment and that their performance rank differ across test sites. The significant effect of GEI have been noted in several research reports on differents traits, including grain yield, in durum wheat landraces and cultivars [29,80], in line with the resuls of the present study.…”
Section: Plos Onesupporting
confidence: 92%
“…In line with this, the biplot analysis showed that Sinana and Holeta are distinct from Kulumsa, Chefe Donsa, and Akaki. The selection of genotypes and test locations play a significant role in the performances of durum wheat genotypes [78], and similar previous research also revealed the influence of test sites on the yield performance of durum wheat genotypes [16,18,41,[79][80][81][82].…”
Section: Discussionmentioning
confidence: 84%
“…This provides evidence of utilizing these genotypes in breeding programs for enhancing wheat grain yield stability and productivity principally under abrupt climate change and increasing adverse environmental conditions. Similarly, significant variations in the stability of wheat grain yield and specific adaptation for certain genotypes to specific environments were reported by Roostaei et al (2014); Kapoor et al (2020); Alipour et al (2021); Awaad (2021); Omrani et al (2022)…”
Section: Discussionmentioning
confidence: 57%
“…Different statistical procedures are used to explore the stability of assessed genotypes such as Additive main effects and multiplicative interaction (AMMI) ( Gauch, 1992 ), joint regression ( Eberhart and Russell, 1966 ), Wricke’s Ecovalence ( Wricke, 1962 ), and Cultivar superiority ( Lin and Binns, 1988 ). Several researchers assessed the phenotypic stability of yield performance using different statistical procedures and deduced different stability degrees across multi-environment trials ( Mansour et al., 2018a ; Alipour et al., 2021 ; Awaad, 2021 ; Omrani et al., 2022 ). Although several studies assessed yellow rust resistance, heat tolerance, agronomic performance, and yield stability of wheat genotypes severally, additional investigation is needed to assess these biotic and abiotic stresses alongside the agronomic performance.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, genetic loci may be falsely related to traits when there is no authentic associations 15 . The possibility of false positives can increase in GWAS if population structure is not suitably accounted for, therefore evaluation of population structure is critical for any association mapping 36 , 37 . The panel of Iranian wheat accessions in this study was stratified into three groups.…”
Section: Discussionmentioning
confidence: 99%